Effects of Commonly Evolved Solid-Electrolyte-Interphase (SEI) Reaction Product Gases on the Cycle Life of Li-Ion Full Cells. Issue 13 (27th September 2018) - Ma, Yonghui; Feng, Lin; Tang, Ching-Yen; Ouyang, Jia-Hu; Dillon, Shen J
Abstract : In this work, it is found that cycling full cells in Ar, versus static conditions, significantly reduces their rate of capacity fade, which is attributed to the removal of gaseous reaction products from the cell. The presence of gases evolved in situ can account for a large fraction of the total capacity fade exhibited by the static cells tested. In attempt to understand the role of specific gaseous species commonly evolved during cycling, LiMn2 O4 and LiCoO2 based full cells were further cycled in Ar-H2, Ar-CO, Ar-CO2, and Ar-CH4 at reactive gas compositions between 0.5% and 5% and flow rates high enough to rapidly remove any evolved gas. The different electrodes were sensitive to different gases, the effects of gas composition were non-linear, and the effect of mixing gases was not additive. An attempt was made to correlate the degree of capacity fade with the amount of transition metal deposited on the anode, as measured by secondary ion mass spectrometry, but a strong correlation was not found.